The Structure and Morphology of Uric Acid by Orthosiphon Aristatus - Yuni Warty; Dewi Wulandari; Eviyona Laurante Br Barus (Jurnal Penelitian Pendidikan IPA, 2025)
Urolithiasis is stone-like material that settles in the urinary tract. The materials that make up urinary stones are calcium oxalate, uric acid, cystine and stuvite. Several medical procedures are often applied to cure this disease. However, many patients choose traditional treatment by consuming herbal medicine. The aim of this research is to show the structure and morphology of uric acid with Orthosiphon Aristatus. This is very important to study as a basis for producing herbal medicines in nanometer sizes. Samples were prepared before characterization.  Urid Acid and Orthosiphon aristatus samples were weighed at a ratio of 0.1: 0.5 milligrams and dissolved in 100 milliliters of Aquabides. The samples were then characterized using XRD and SEM-EDX uric acid crystals mixed with Orthosiphon aristatus undergo progressive dissolution, characterized by an increasingly smooth surface and smaller particle size over time. The particle diameter of each sample changed from 37.64 to 32.83. This research will contribute to urinary stone sufferers choosing appropriate traditional medicine for the type of urinary stone they have